ANALISIS PERPUTARAN MODAL KERJA DAN RETURN ON INVESTMENT PADA PT ADI SARANA ARMADA Tbk. - -, Melany Sumari (EKONOMIA, 2014)
Analysis And Return On Investment In Tbk PT Adi Sarana Armada,  Formulation of the problem is working capital turnover and return on investment increased in 2011 and 2012. This study was to determine the velocity of working capital and return on investment. The analytical tool used is working capital turnover, receivables turnover, Inventory Turnover and Return On Investment.               The relationship between the Return On Investment by working capital turnover is turn over is turnover of working capital is the ratio between sales and net working capital of a company for a certain period. Relationship with the working capital turnover rate of profitability can be seen from how effectively the company uses working capital generated in the form of sales, the higher the level of sles of a company, the higher the working capital will certainly increase its profit would affect the Return On Investment.              Based on the results show that the cash turnover in 2012 decreased by 5,94 times, accounts receivable turnover in 2012 increased by 2,234 times, inventory turnover in 2012 decreased by 39,53 times, working capital turnover 17,47 times and return on investment also increased by 0,007%. The higher the level of sales of company, the higher the working capital wiil certainly increase its profit would affect the Return On Investment.